Analisis Pengendalian Internal Terhadap Penyaluran Kredit Usaha Rakyat (KUR) pada PT Bank Pembangunan Daerah Jawa Tengah Kantor Cabang Pembantu Babadan Ungaran - Franciska Denanda Rika Widiharsanti; Mochammad Abdul Kodir; Embun Duriany Soemarso (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2023)
Internal control in a company is very important. Internal control will be used by the company as a guide in carrying out its operational activities. The purpose of this study was to determine the application of the internal control system in distributing people's business credit (KUR) implemented by PT Bank Pembangunan Daerah Jawa Tengah, Babadan Ungaran Sub-branch Office and to identify whether the internal control applied is in accordance with the control components according to the Committee of Sponsoring Organizations of The Treadway Commission (COSO), which includes the control environment, risk assessment, control activities, information and communication, and monitoring. The data used is qualitative data sourced from primary data and secondary data. Collecting data using interviews, questionnaires, and literature study. The writing method uses a descriptive qualitative method. The results of this study indicate that the implementation of the internal control system for the distribution of people's business loans (KUR) at PT Bank Pembangunan Daerah Jawa Tengah, Babadan Ungaran Sub-Branch Office has gone very well and the suitability of internal control components with internal control components according to the Committee of Sponsoring Organizations of the The Treadway Commission (COSO) has not fully complied with the risk assessment component, there are still bad credit and human error. Keywords: Internal Control System, Distribution of People's Business Credit, Standard Committee of Sponsoring Organization of The Treadway Commission (COSO)